Karakterisasi Senyawa Flavonoid Ekstrak Polar Daun Gamal Kultivar Lampung Utara Dan Uji Aktivitasnya Terhadap Kutu Putih Kakao (Planococcus minor, Hemiptera: Pseudococcidae) - Nukmal, Nismah; Pasutri, Agata Yelin; Pratami, Gina Dania (Bioma : Berkala Ilmiah Biologi, 2019)
Cocoa is one of the export commodities that have great prospects. The quality of cocoa in Indonesia are not satisfactory, this is caused by cocoa mealybug (Planococcus minor). Gamal (Gliricidia maculata) contains flavonoid compounds which can be used as bioinsecticides. The aims of research to determine the characteristic of flavonoid compounds in gamal leaf powder which is effective for kill of cocoa mealybug P. minor. Extraction and spectroscopy analysis (UV-Vis and FTIR) were done in the Integrated Laboratory of Technology Innovation Center (ILTIC) and the bioassay was done at Zoology Laboratory of Unila. The results shows that the crude water extract of gamal leaf powder North Lampung Cultivar (NLC) more effective killed lower than purified water extract. It was indicated by value of LC50.72hours the crude water extract than purified water extract (0.11%: 0.27%). The flavonoid compounds of gamal leaf powder NLC have the characteristics of blue fluorescence in UV light Î» 254 and 366 nm. The flavonoid with the maximum peak of wavelength 310 could be grouped to flavonone with structural frame O-H, C=O carbonyl, aromatic C=C, and C-O.